Analysis of Operation and Possibilities of Improving E-Learning System in Traffic Engineering - Peraković, Dragan; Remenar, Vladimir; Šašek, Zdravko (Promet - Traffic&Transportation, 2007)
Since the Faculty of Transport and Traffic Sciences wasconnected to CARNet academic network, new informationand communication technologies are constantly being introducedand the old ones updated with the aim of improving thequality of studying, from the introduction of WEBCT applicationto complete design, development and implementation ofone’s own solution of e-leaming. A complete e-Learning systemhas been developed, named e-Student which consists of severalprogram modules called SAN, DMS, SMSCentar, etc. Sincethe introduction of the system, the students and the teachingstaff have shown great interest for the system for the reasons ofeasier monitoring of the students’ activities, through seminarpapers and tasks, exercises and throug h solving of variousknowledge tests. The work provides graphical illustrations andstatistical data which analyze the operation of the system andthe exploitation characteristics. The obtained results indicatethe increase in the interest of the teaching staff and studentswhich indicates further need to upgrade the system in order toincrease the safety and speed of information transfer.